2003
DOI: 10.1097/01.fbp.0000081785.35927.08
|View full text |Cite
|
Sign up to set email alerts
|

Contingent and noncontingent cocaine administration in rhesus monkeys: a comparison of the effects on the acquisition and performance of response sequences

Abstract: Previous studies have suggested that the effects of contingent (response dependent) and noncontingent (response independent) cocaine administration may differ, which could limit the generality and validity of laboratory studies that use only noncontingent administration. Therefore, two separate three-component multiple schedules of operant responding were used to examine the effects of both types of cocaine administration on the acquisition and performance of response sequences, in four rhesus monkeys. In one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…After a longer withdrawal period from cocaine exposure with a non-contingent cocaine history, a decrease in intrinsic excitability occurs in MSNs, at least in the shell compartment. However, previous studies have also suggested that the effects of contingent and non-contingent cocaine administration may differ quantitatively or qualitatively, which could limit the generality and validity of laboratory studies that use primarily non-contingent administration (Winsauer et al, 2003). Only a handful of studies have examined the functional output of NAc MSNs in the cocaine contingent administration model (Mu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After a longer withdrawal period from cocaine exposure with a non-contingent cocaine history, a decrease in intrinsic excitability occurs in MSNs, at least in the shell compartment. However, previous studies have also suggested that the effects of contingent and non-contingent cocaine administration may differ quantitatively or qualitatively, which could limit the generality and validity of laboratory studies that use primarily non-contingent administration (Winsauer et al, 2003). Only a handful of studies have examined the functional output of NAc MSNs in the cocaine contingent administration model (Mu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The resultant behavioral and neurochemical effects should be interpreted predominantly as a function of exposure to the METH and AMPH plasma concentrations that were achieved with passive drug administration throughout this study, since qualitatively different behavioral and/or neurochemical consequences may sometimes occur depending on whether the stimulant is self- or experimenter-administered (see, for example (Stefanski et al, 1999; Jacobs et al, 2003), although see (Winsauer et al, 2003; Kiyatkin and Brown, 2004; Stuber et al, 2005))…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous animal studies report a variety of physiological and neurochemical distinctions between contingent and noncontingent cocaine exposure (Wilson et al 1994;Hemby et al 1997;Broadbear et al 1999;Kuzmin and Johansson 1999;Galici et al 2000;Porrino and Lyons 2000;Crespo et al 2002;Smith et al 2003), it is relatively unknown if these physiological and neurochemical differences have functional behavioral consequences. For example, it was reported that the effects of cocaine on complex operant behavior in monkeys did not differ substantially as a function of contingent or noncontingent drug administration (Winsauer et al 2003).…”
Section: Introductionmentioning
confidence: 99%